The Outpatient Treatment of Venous Thromboembolism: Operational Impact and the Role of Novel Anticoagulants - White, Benjamin; Rosovsky, Rachel; Parry, Blair Alden; Kabrhel, Christopher (Seminars in Thrombosis and Hemostasis, 2016)
Pulmonary embolism (PE) and venous thromboembolism (VTE) are common diagnoses in the emergency department (ED), with significant potential morbidity and mortality. As a result, historically nearly all patients with PE have been admitted to the hospital for observation and treatment. In recent years, the ability to rapidly and accurately risk stratify patients with VTE according to their risk of short-term clinical deterioration has supported outpatient treatment, and non-vitamin K antagonist oral anticoagulants (NOACs) have further facilitated this approach. This review details the historical context and operational impact of managing VTE in the outpatient setting, describes a model for outpatient management of VTE, and suggests potential areas of further inquiry.
Keywords: pulmonary embolism; venous thromboembolism; anticoagulation; emergency department operations; outpatient treatment